A house accursed: reconsidering Sophocles' sisters, Antigone & Ismene - Fox, Peta Ann,Sophocles (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
Traditionally, Ismene's refusal to help Antigone bury their brother in Sophocles' Antigone tends to be regarded only in relation to Antigone's own remarkable bravery. Antigone exists on the heroic level, Ismene on the ordinary; Antigone is courageous, Ismene is timid and submissive; Antigone is an idealist and an individualist, Ismene is convention and herd-bound. Ismene is, in many ways, presented as the antithesis of Antigone and Sophocles does indeed make use of her character as a foil to Antigone, but this thesis will argue that the relation between the two sisters is far more complicated than a dichotomous contrast between 'extraordinary heroine' and 'average woman'. Like Antigone, Ismene is very much a character in her own right, and her emotions, motivations and impulses are every bit as realised and compelling as Antigone's own. Both sisters have been deeply affected by the tragic misfortunes of their family, but their sad history affects each sister quite differently. Whereas Antigone's instinctive reaction to Creon's edict is a furious determination not to tolerate any further dishonour, Ismene's equally instinctive reaction is to avoid the pattern of self-destructive inwardness that has plagued their family for generations. By offering a comprehensive re-examination of the key passages that have informed our critical reception of Ismene and the nature of her relationship with Antigone, this study aims to disrupt the established, and largely prejudiced, reading of Ismene as a model of feminine timidity and submission. Although Ismene is certainly no grand tragic heroine, titling the theoretical focus away from the death-oriented extremism of Antigone towards a more balanced consideration of the so-called 'weaker sister' not only allows for new insights into the nature of Sophoclean tragedy, but also challenges the very basis on which Ismene has so often been dismissed in favour of her more intrepid sister: the pervasive assumption that Sophocles has only given us one sister who is willing to risk her life for a principle.
Keywords: Ismene (Greek mythology); Antigone (Greek mythological figure); Electra (Greek mythological figure); Chrysothemis; Greek tragedy; Sisters in literature